Variation in the Sizes of Chthamalid Barnacle Post-Settlement Cyprids on European Shores - O'Riordan, Ruth M. (2001)
As part of a wider study on the settlement and recruitment of Chthamalus spp. in Europe, this study investigated whether chthamalid cyprids can be separated by length on a European scale. Variation in cyprid length with latitude and temporal varia- tion at selected localities were also examined. The lengths of cyprids collected between 1996±1999 on nine rocky shores in Europe are reported. Elminius modestus cyprids were found only at Roscoff, NW France and could be distinguished due to their cara- pace shape and length. They showed a unimodal length distribution, measuring be- tween 450 and 625 mm, with no variation in length between the two sampling dates (1997 and 1998). Based on carapace shape and length, the remaining cyprids in the col- lections were identified as one of three chthamalid species, Chthamalus montagui, Chthamalus stellatus or Euraphia depressa. Bimodal length distributions of chthamalid cyprids were seen on some shores, while others had a single small-sized modal group (representing C. montagui on Atlantic shores and/or E. depressa in the Mediterranean)